Aplicación de protocolos de manejo y cuidados y su beneficio en el sistema inmunológico de pacientes traqueostomizados de la unidad de cuidados intensivos del Hospital de Infectología de Guayaquil mayo-septiembre 2019. - Moreta García, Glenda Elizabeth (2019)
A tracheostomy is performed in order to maintain the permeability of the airway or establish an artificial airway to ensure patient ventilation, and these patients need special care before, during and after the procedure, therefore the driving protocols and care are of great importance for each of these patients. General Objective: To identify the benefits acquired with the application of the management and care protocols on the immune system of tracheostomized patients in the intensive care unit of the Infectology Hospital of Guayaquil. Methodology: The methods that were used for the elaboration of this thesis were the Deductive one and the one of Synthesis. The modality that was used for this research was qualitative and quantitative and the type of research chosen was Non-Experimental, Descriptive and Transversal. Results: The data obtained show that adequate asepsis in the tracheostomized patient can prevent the acquisition of new diseases, the tracheostomy procedure is frequently performed in this hospital in the ICU areas, 73% of respondents if they believe that applying the Management and care protocols prevent depression of the immune system in tracheostomized patients, with the application of protocols in tracheostomized patients prevent nosocomial infections. Conclusions: The tracheostomy procedure is frequently implemented in the infectious hospital of Guayaquil but in these patients a predominant effect arises which is the depression of their immune system.